Judicial Power and Judges’ Status in Indonesia’s Constitutional Framework - Adies Kadir; Gunarto Gunarto; Suwarno Suwarno; Md Adnan Kabir (Unissula, 2025)
This study aims to analyze and formulate the ideal concept of regulating the position of judges as State Officials from the perspective of ius constituendum, by considering the principle of the rule of law adopted by Indonesia. In the Indonesian constitutional system, Article 24 of the 1945 Constitution affirms the judicial power that is independent and free from interference by other powers. However, reality shows that the dualism of the judge's status—as a civil servant and state official—causes ambiguity in the personnel system, administration, and judicial independence. This study uses a normative approach with a qualitative legal analysis method, supported by a philosophical and legislative approach. The results of the study show that the status of judges should be consistently recognized as State Officials to strengthen independence, professionalism, and integrity in carrying out judicial functions. Philosophically, the independence of judges reflects the noble values of Pancasila and the principle of Belief in the One Almighty God, as contained in the court rulings. Therefore, it is necessary to formulate new regulations that eliminate dualism of status and ensure institutional protection for judges. It is hoped that this conceptual reformulation can become the basis for the formation of legislation that is fairer, more progressive and in accordance with the ideals of Indonesian law.